Differences - Wright, John; Taylor, John; McKay, Doug; Foon, Dennis, 1951-; Hall, Raymond (National Film Board of Canada, 1986)
A short drama examining the racial conflicts that can occur among children when an "outsider" appears in the midst of a dominant culture. Chris, a pre-adolescent, resents the visit of Emma, a native girl to his home.